A STUDY ON EFL STUDENTS’ WRITING ANXIETY (A CASE STUDY OF THE INDONESIAN STUDENTS) - Ari Rahmad Nawawi; Rahmadi Nirwanto; Hesty Widiastuty (PROJECT (Professional Journal of English Education), 2024)
This research aimed at investigating (i) internal factors; (ii) external factors which affect students’ writing anxiety in English language learning. Qualitative research method was used to gain the data from participants. The participants were 20 students of English education study program of a State Islamic Institute in Palangka Raya, Central Kalimantan, Indonesia who have already passed Academic Writing Course. The researchers adopt non probability sampling, namely, purposive sampling in recruiting participants. The data were collected through structured and unstructured interviews and data were analyzed through content analysis. The findings indicate that the internal factors include lack of experiences in writing process; external factors include time pressure, ways of evaluation, and linguistic difficulties. Internal factors and external factors in this research become the reasons why students feel anxious in the writing process especially in English language learning.